Pattern and types of non-saphenous vein reflux. (March 2013) - Malgor, R D; Labropoulos, N
Venous reflux often originates from saphenous trunks and their tributaries. In about 10% of the patients reflux derived from non-saphenous veins (NSV) such as those located in the buttock, posterolateral thigh, vulva, lower posterior thigh, popliteal fossa, knee or along the peripheral nerves such as the tibial and sciatic nerve. It is also important to note that patients who had saphenous vein stripping or ablation have higher odds of presenting with NSV reflux. The majority of patients with NSV reflux have varicose veins and lower extremity oedema; however, about 10% of those patients present with skin damage. This paper analyses the patterns and types of NSV reflux for diagnosis and treatment purposes.